2012
DOI: 10.3892/mmr.2012.1117
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells from vitiligo perilesional margins induce autologous melanocyte apoptosis

Abstract: Cell-mediated autoimmunity has been suggested to be involved in the melanocyte apoptosis that occurs in vitiligo. We investigated the cytotoxicity to autologous melanocytes of CD8+ T cells from the perilesional margins and peripheral blood samples of vitiligo patients. CD8+ T cells isolated from skin biopsied from the edges of depigmented skin patches of vitiligo patients or from peripheral blood samples of the same donors were proliferated in culture medium. The primary cultures of CD8+ T cells and autologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 36 publications
0
43
0
1
Order By: Relevance
“…In addition, several studies have identified a pivotal role for cytotoxic T cells in inducing melanocyte-specific destruction in vitiligo [7], including the findings that CD8 + T cells isolated from vitiligo skin are cytotoxic to melanocytes, recognise melanocyte-specific autoantigens [7], and induce autologous melanocyte apoptosis through IL-6 and IL-13 [9] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have identified a pivotal role for cytotoxic T cells in inducing melanocyte-specific destruction in vitiligo [7], including the findings that CD8 + T cells isolated from vitiligo skin are cytotoxic to melanocytes, recognise melanocyte-specific autoantigens [7], and induce autologous melanocyte apoptosis through IL-6 and IL-13 [9] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, CD8+ T cell-mediated melanocyte destruction has been demonstrated in vitiligo. In addition, an increased accumulation of CD8+ T cells in peripheral blood mononuclear cells (PBMCs) and perilesional skin of patients with progressive vitiligo has been reported (1,3). On the other hand, elevated expression of Th1 cell specific transcription factor (T-bet) and cytokine (IFN-γ) was indicated in PBMCs of patients with vitiligo (2).…”
Section: Dear Editormentioning
confidence: 99%
“…Cytotoxicity via induction of apoptosis has been considered as a major effector mechanism of autoreactive CTLs. Therefore, recruited CD8+ T cells may specifically induce autologous melanocyte apoptosis resulting in disappearance of melanocytes (3). On the other hand, CD4+ Th1 cells (one of the main sources of IFN-γ production) are required for optimal induction of antigen-specific CD8+ T cell effector responses.…”
Section: Dear Editormentioning
confidence: 99%
“…Still, plasmacytoid dendritic cells, which are part of the perilesional cellular infiltrate and the major IFN-α-producing cell subset, may sustain the recruitment and activation of T cells (Bertolotti et al, 2014). In support of this mechanism, apoptosis in vitiligo melanocytes has also been demonstrated (Wu et al, 2013).…”
mentioning
confidence: 96%